Pendidikan hukum sebagai upaya membangun kesadaran hukum masyarakat - Adi Nur Aziz; Ayu Maya Damayanti; Rofiko Fauzia; Maulidia, Nike (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low level of public legal awareness and compliance remains a serious problem in social and national life. This condition has resulted in increased legal violations and a decline in public trust in the law itself. One effort that can be made to overcome this problem is through continuous and systematic legal education. This study aims to analyze the role of legal education in building public legal awareness and assess the effectiveness of legal education in increasing public compliance with the law. The research method used is a normative juridical method with a conceptual and legislative approach, supported by a library study of various literature, scientific journals, and relevant legal regulations. The results of the study indicate that legal education plays a strategic role in instilling legal values, increasing public understanding of their rights and obligations, and shaping law-abiding attitudes and behavior. Legal education conducted through formal, non-formal, and informal channels has been proven to be able to increase public legal awareness when accompanied by effective socialization and role models from law enforcement officers and community leaders. Furthermore, the effectiveness of legal education in increasing legal compliance is greatly influenced by the consistency of law enforcement and the relevance of legal education materials to social realities. Thus, legal education is a crucial instrument in creating a legally aware, orderly, and just society.